Correction: Global spectral and local molecular connects for optical coherence tomography features to classify oral lesions towards unravelling quantitative imaging biomarkers. Issue 48 (29th April 2016) - Banerjee, Satarupa; Chatterjee, Swarnadip; Anura, Anji; Chakrabarty, Jitamanyu; Pal, Mousumi; Ghosh, Bhaskar; Paul, Ranjan Rashmi; Sheet, Debdoot; Chatterjee, Jyotirmoy
Abstract : Correction for 'Global spectral and local molecular connects for optical coherence tomography features to classify oral lesions towards unravelling quantitative imaging biomarkers' by Satarupa Banerjee et al., RSC Adv., 2016, 6, 7511–7520.